2020
DOI: 10.1093/ajhp/zxaa342
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of a multidisciplinary workflow on safety and management of patients with heparin-induced thrombocytopenia

Abstract: Purpose Heparin-induced thrombocytopenia (HIT) is a serious complication of heparin administration. Management strategies are complex and include discontinuing heparin products, initiating alternative anticoagulants, interpreting laboratory test results, documenting heparin allergies, and providing patient education. Medication error reports and a retrospective review conducted at an academic medical center revealed an opportunity for a quality improvement initiative and led to the creation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This is relevant because unaccounted for residual heparin could result in inadvertent detection of heparin-dependent antibodies. The authors point out that ongoing heparin administration occurrs in approximately half of patients whose blood is referred for HIT diagnostic testing [192]. Further, one study [58] found residual heparin (at least 0.1 IU/mL) was present in 62% of samples referred for HIT testing.…”
Section: Technical Challengesmentioning
confidence: 99%
“…This is relevant because unaccounted for residual heparin could result in inadvertent detection of heparin-dependent antibodies. The authors point out that ongoing heparin administration occurrs in approximately half of patients whose blood is referred for HIT diagnostic testing [192]. Further, one study [58] found residual heparin (at least 0.1 IU/mL) was present in 62% of samples referred for HIT testing.…”
Section: Technical Challengesmentioning
confidence: 99%
“…Our observation that heparin contamination was noted in approximately half of all diagnostic HIT samples is consistent with published findings that heparin administration continued in 54% of patients while HIT testing results were pending. 13 In a recent study, anti-Xa activity testing in a cohort of diagnostic HIT samples demonstrated that contaminating heparin (anti-Xa activity ≥ 0.1 IU/mL) was detected in 21 of 34 (62%) samples. 14 In that study, a comparison of outcome severity in confirmed heparin-negative samples with an aHIT profile (ie, activation in the no-heparin SRA) vs classical HIT demonstrated no differences in platelet nadir or persistence of thrombocytopenia.…”
mentioning
confidence: 98%
“…On the basis of unfractionated heparin (UFH) half-life of 60-90 min [3], our hospital recommends stopping UFH administration at least 8 h prior to testing for HIT. However, samples are often collected sooner or even while the patient is still receiving UFH [4]. It has been reported that therapeutic levels of UFH may interfere with functional HIT assays, such as the serotonin release assay [5,6].…”
mentioning
confidence: 99%